Penalaran Matematis: Pembiasaan Soal High Order Thinking Pada Siswa Usia Sekolah Dasar - Octarina Hidayatus Sholikhah; Amalia Chamidah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
The purpose of the article is to create a mathematical reasoning modeling framework through working on high order thinking questions for elementary school students. The modeling cycle (formulating, applying, interpreting, and evaluating) is a central aspect of the conception of mathematical reasoning for students for the sake of mathematical literacy. Formulating is an individual's ability to recognize and identify opportunities to use mathematics and then provide a mathematical structure for problems presented in several contextual forms. Applying is an individual's ability to apply concepts, facts, procedures, and mathematical reasoning to solve mathematically formulated problems in order to obtain mathematical conclusions. Interpreting and evaluating (interpret and evaluate) is the individual's ability to reflect on mathematical solutions, results or conclusions and interpret them into the context of real life problems. This is a literature study, the data was collecting using literature studies on scientific journal articles and news about mathematical reasoning, high order thinking, and numeracy. The modeling cycle is recommended for teaching mathematics in elementary school through series of problem solving stages in questions with higher order thinking skill concept.